(untitled) (International Journal of Engineering and Computer Science, 2014)
Image fusion in the field of remote sensing deals with combination of multispectral and panchromatic image. The idea of such combination is to derive best information out of it. A multispectral image is spectral rich whereas a panchromatic image is spatially sound so their combination gives better information in terms of best spatial and spectral parameters. This Paper aims at evaluating various fusion methods available so far and helps to analyze the comparisons between them. To determine the best approach it must have high computational efficiency, preserve the high spatial resolution and minimize the color distortion